Analytical model and parametric study for externally post-tensioned reinforced concrete-steel composite beams. (October 2020) - El-Zohairy, Ayman; Alsharari, Fahad; Salim, Hani
Abstract: An active strengthening technique by external post-tensioning (PT) can be effectively used to improve the flexural performance of reinforced concrete (RC)-steel composite beams (CB) under static loads. In this research, an analytical model is proposed, where the nonlinear material behaviors of steel and concrete are adopted. The proposed analytical model is carried out by the computer software MATLAB to run the iterations to satisfy the equilibrium of the internal forces in the post-tensioned composite sections. Static tests on two full-scaled RC-steel CB are also presented to calibrate the proposed model. The testing measurements included deflections, strains in the extreme fibers of the composite sections, and the incremental PT force in the tendons. Finally, the most significant parameters that affect the bending capacity and stiffness of the post-tensioned CB are assessed by conducting an extensive parametric study. These parameters include the influence of steel beam grade, axial forces, and concrete deck width and strength. The contribution of the external PT force to improve the CB behavior is enhanced by using stainless steel for steel beams. However, the post-tensioned CB with conventional carbon steel shows higher stiffness and capacity over that one with stainless steel and more ductility over the other one with high-strength steel (HSS). At a low level of axial compressive force, the un-strengthened CB show a double improvement in the flexural strength over the strengthened ones. Whereas, the difference between the two behaviors diminishes as the axial compressive force increases.